Liquid Silicone Injection Moulding: Revolutionizing Nasal Splint Development for Improved Patient Outcomes - Dr. Pramod Kumar, Minocha; Mahendralal, Kothwala Dr. Deveshkumar; Yogendrasinh, Lodha Dikshita; Nanjibbhai, Hadia Meet; Samir, Desai Mansi (International Journal of Innovative Research in Medical Science, 2024)
Maintaining a healthy nose is critical to overall well-being, especially for individuals undergoing rhinoplasty or septoplasty, where nasal splints play an important role in promoting recovery and minimising postoperative bleeding. This study looks at the potential of liquid silicone resin (LSR) in the manufacture of nasal splints, with a particular focus on the LSR moulding method. LSR, which is known for its easy flowability, precision and fast drying, proves to be an ideal material for the development of internal nasal splints. The use of LSR not only improves the quality of the resulting products, but also speeds up the manufacturing process. Laboratory-scale tests have been conducted to verify the safety and effectiveness of nasal splints produced using LSR moulding technology. The field of LSR moulding continues to evolve, positioning liquid silicone injection moulding as the primary method for manufacturing nasal splints and other medical devices. This study provides valuable insight into the versatile applications of LSR and paves the way for innovative solutions for nasal health. By exploring the possibilities of LSR in the manufacture of nasal splints, this study provides a comprehensive understanding of the potential advances in medical device manufacturing, contributing to continued progress in the field.